Prevalence of E. coli ST131 among Uropathogenic E. coli Isolates from Iraqi Patients in Wasit Province, Iraq - Dhifar Raa’d Al-Guranie; Sareaa Maseer Al-Mayahie (International Journal of Microbiology)
The emergence of Escherichia coli sequence type 131 (E. coli ST131) clone represents a major challenge to public health globally, since this clone is reported as highly virulent and multidrug-resistant, thus making it successfully disseminated worldwide. In Iraq, there is no previous study dealing with this important clone, so this project was suggested to investigate its presence within uropathogenic E. coli (UPEC) from Iraqi patients in Wasit Province. A total of 112 UPEC isolates from cases of acute urinary tract infection (UTI) were analysed for phylogenetic groups by quadruplex PCR; then, these isolates were investigated for E. coli ST131 clone by both conventional and real-time PCR procedures. The antibiotic susceptibility test was performed by the disk diffusion method. The results revealed that, out of 112 UPEC isolates, 38 (33.9%) belonged to phylogroup B2. For conventional PCR, 92.1% (35/38) of B2 E. coli isolates were positive for E. coli ST131, of which 34 were O25b-ST131 strain and 1 was O16-ST131 strain. However, serogroups O25b and O16 represented 17.1% and 2.8%, respectively. By RT-PCR assay, 15.1% (17/112) and 44.7% (17/38) of total and B2 E. coli isolates were confirmed as being E. coli ST131, respectively. The highest resistance rates of E. coli ST131 isolates were against the β-lactams, while low resistance rates were against amikacin, nitrofurantoin, and gentamicin. Fortunately, all isolates were susceptible to carbapenems. Moreover, 52.9% (9 out of 17) of E. coli ST131 isolates were MDR. In conclusion, the presence of E. coli ST131 among UPEC isolates from Iraqi patients is confirmed with high resistance to most antimicrobials included in this study.